دراسة سببية لنزوف الخلاص للولادات الطبيعية - عبد الرحمن أحمد; محمد باسل (Latakia University Journal -Medical Sciences Series, 2017)
أجري هذا البحث لدراسة جميع الأسباب المؤدية لنزوف الخلاص بهدف تطبيق كافة المعالجات المناسبة حسب كل سبب وبالتالي تجنب اختلاطات نزوف الخلاص والوفاة ، ودراسة عوامل الخطورة لحدوث النزف بهدف الوصول لأفضل طريقة للوقاية والاستعداد له ومنع حدوث النزف أو الإقلال منه . اشتمل هذا البحث على 77 مريضة مقبولة في مشفى الأسد الجامعي باللاذقية وشخص لديها نزف خلاص بدئي حدثت بعد ولادة مهبلية ، منها ( 12 ) حالة نزف خلاص بعد ولادة مهبلية تمت خارج المشفى ، خلال فترة الدراسة الممتدة : من 1/1/ 2014حتى 1/1/ 2016 ، واستبعدنا فقط المريضات اللواتي ولدن بقيصرية . حيث تم تحديد نسبة حدوث نزوف الخلاص بين الولادات المهبلية في المشفى ، وبلغت النسبة (3,52 %) ، ولم نتمكن من تحديد نسبة حدوث نزوف الخلاص خارج المشفى. وتم دراسة جميع الأسباب المؤدية لنزوف الخلاص ، و أكثر هذه الأسباب شيوعاً هي العطالة الرحمية وبنسبة (48,05 %) ، وتلاها تمزقات ورضوض المسير التناسلي بنسبة (31,17 % ) ، ثم احتباس المشيمة الجزئي أو الكلي بنسبة (11,69 % ) ، أما انقلاب باطن الرحم لظاهره فكان أقل الأسباب حدوثا ً حيث وجدنا حالتين فقط بنسبة (2,60 % ) . وقسمت الحالات المدروسة حسب درجة النزف إلى نزف خلاص خفيف ومتوسط وشديد ، ودرست العلاقة بين سبب النزف ودرجته (p-value أقل من 0,05 ) ، فكانت أغلب حالات نزف الخلاص الخفيف بسبب العطالة الرحمية ، وأغلب حالات نزف الخلاص الشديد بسبب رضوض المسير التناسلي. This research was conducted to study all the causes leading to postpartum hemorrhage in order to implement all the appropriate treatments, according to all reason and thus avoiding the complications of postpartum hemorrhage and death, and study of the risk of bleeding factors in order to reach the best method of prevention of bleeding . This research included on 77 patient acceptable in Al Assad University Hospital in Lattakia, with primary postpartum hemorrhage occurred after vaginal delivery, including (12) patient after vaginal birth outside the hospital, during the extended study period: from 1/1/2014 until 1/1 / 2016, and excluded all patients who were born cesarean delivery. We determine the percentage of postpartum hemorrhage occurring between vaginal deliveries in the hospital, and the ratio was (3.52%), and we could not determine this percentage outside the hospital. It was studied all the leading causes of postpartum hemorrhage , and most of these common causes are uterine atony and by (48.05%), followed by lacerations and bruises of genital truct rate (31.17%), and retained placental tissues rate of (11.69%) , while uterine inversion was less frequent causes where we found only two cases by (2.60%). Then , we divided the studied cases by the degree of bleeding to mild hemorrhage, medium and severe, and studied the relationship between the bleeding cause and its degree (p-value less than 0.05), the most cases of mild bleeding was because of uterine atony, and most cases of severe bleeding was because of bruises of genital truct .